Loss of olfaction in sea snakes provides new perspectives on the aquatic adaptation of amniotes - Kishida, Takushi (Proc Biol Sci, 2019)
Marine amniotes, a polyphyletic group, provide an excellent opportunity for studying convergent evolution. Their sense of smell tends to degenerate, but this process has not been explored by comparing fully aquatic species with their amphibious relatives in an evolutionary context. Here, we sequenced the genomes of fully aquatic and amphibious sea snakes and identified repertoires of chemosensory receptor genes involved in olfaction. Snakes possess large numbers of the olfactory receptor (OR) genes and the type-2 vomeronasal receptor (V2R) genes, and expression profiling in the olfactory tissues suggests that snakes use the ORs in the main olfactory system (MOS) and the V2Rs in the vomeronasal system (VNS). The number of OR genes has decreased in sea snakes, and fully aquatic species lost MOS which is responsible for detecting airborne odours. By contrast, sea snakes including fully aquatic species retain a number of V2R genes and a well-developed VNS for smelling underwater. This study suggests that the sense of smell also degenerated in sea snakes, particularly in fully aquatic species, but their residual olfactory capability is distinct from that of other fully aquatic amniotes. Amphibious species show an intermediate status between terrestrial and fully aquatic snakes, implying their importance in understanding the process of aquatic adaptation.